       Re: Full simplify problem

• To: mathgroup at smc.vnet.net
• Subject: [mg122280] Re: Full simplify problem
• From: dimitris <dimmechan at yahoo.com>
• Date: Sun, 23 Oct 2011 06:24:23 -0400 (EDT)
• Delivered-to: l-mathgroup@mail-archive0.wolfram.com
• References: <j7u59t\$u\$1@smc.vnet.net>

```On Oct 22, 1:18 pm, "A. Lapraitis" <ffcita... at gmail.com> wrote:
> Hello,
>
> Could anyone explain why the following does not give zero?
>
> In:= Assuming[
>  x == y + z,
>  FullSimplify[
>   E^x - E^(y + z)
>   ]
>  ]
>
> Out= E^x - E^(y + z)
>
> Thanks!

Hello again.

Apart from my original reply I would also like to add the following
attempt which generates a message but
does what you wanted.

Assuming[x === y + z, FullSimplify[E^x - E^(y + z)]]
\$Assumptions::fas:Warning: One or more assumptions evaluated to False.
0

?===
lhs === rhs yields True if the expression lhs is identical to rhs, and
yields \
False otherwise.

But I do consider my first attempt the best one (and I finally
understood that this is a normal behavior of FullSimplify thanks to
Mr  Kozlowski).

Dimitris

```

• Prev by Date: Re: how do you prevent numerator expansion when using 'Together'?
• Next by Date: Re: strange error
• Previous by thread: Re: Full simplify problem
• Next by thread: Re: Full simplify problem